Nuclear Receptor Coactivator 2 Promotes Human Breast Cancer Cell Growth by Positively Regulating the MAPK/ERK Pathway - Cai, Mengjiao; Liang, Xin; Sun, Xiao; Chen, Huan; Dong, Yiping; Wu, Lingzhi; Gu, Suxi; Han, Suxia (Frontiers in Oncology, 2019)
As a member of the p160 steroid receptor coactivator (SRC) gene family, nuclear receptor coactivator 2 (NCOA2) is known to play essential roles in many physiological and pathological processes, including development, endocrine regulation and tumorigenesis. However, the biological functions of NCOA2 in breast cancer is not fully understood. We found that the copy number of NCOA2 gene was frequently amplified in four breast cancers datasets, varying from 6% to 10%, and the mRNA levels of NCOA2 were also upregulated in 11% of the sequenced cases/patients (TCGA provisional dataset). Next, we confirmed that shRNA-mediated NCOA2 knockdown significantly suppressed cell proliferation in different breast cancer cell lines, accompanied with cell cycle arrest and significant apoptosis. Mechanistically, a whole-transcriptome sequencing (RNA-Seq) analysis uncovered that NCOA2 depletion leads to downregulated MAPK/ERK signaling cascade, possibly via downregulating NCOA2’s downstream gene RASEF. In conclusion, our results suggest NCOA2 as a potential target of therapeutics against breast cancer.